PENENTUAN ARAH DAN KECEPATAN AIR TANAH DANGKAL DISEKITAR BANGUNAN DENGAN MENGGUNAKAN TEKNIK SUMUR TUNGGAL - ., SUGIARTO; ., MARDIANA (FORUM BANGUNAN, 2012)
The problem of ground water is a thing often becomes an obstacle for civil engineers in planning a construction project carefully and thoroughly. Therefore it is necessary for a study that could provide clear information on the state of the local ground water in order to produce a more accurate planning. The purpose of this study is to determine the direction and velocity of shallow groundwater wells using a single technique and combined with a radioactive tracer technique. In a single well technique, used as a tracer radioactive I 131 (tracer) and a drill wells as observation wells. This research was carried out behind the building and geothermal hydrology group P3TIR Nuclear Energy Agency Cinere Pasar Jumat Street, South Jakarta. In this study, groundwater velocity values obtained at 0, 5 cm / h and direction of groundwater flow westward.Â